Fluorescence studies on some hydroxypyridines including compounds of the vitamin B(6) group - Bridges, J. W. (1966)
1. The variations with pH (from 36n-sulphuric acid to 10n-sodium hydroxide) of the excitation and fluorescence wavelengths and fluorescence intensity of 2-, 3- and 4-hydroxypyridine and their O- and N-methyl derivatives were investigated. 2. 4-Hydroxy- and 4-methoxy-pyridine were non-fluorescent at all pH values. 3. The cations and dipolar ions of the 3-hydroxypyridine derivatives and the anion of 3-hydroxypyridine were fluorescent, but the neutral forms were not. 4. All the forms of the 2-hydroxypyridine derivatives were fluorescent. 5. Pyridoxol, pyridoxal and its 5-phosphate, pyridoxamine and pyridoxic acid and its lactone were studied similarly. All these compounds, except pyridoxal 5-phosphate, were more fluorescent than 3-hydroxypyridine. 6. The most fluorescent forms of these compounds are the anions, except for pyridoxol, where the dipolar ion was the most fluorescent form. The least fluorescent forms are the neutral molecules. The dipolar ions were appreciably fluorescent in all cases. 7. The most fluorescent form examined was the dianion of pyridoxic acid lactone. 8. The cations were all fluorescent except the cations of 2- and 3-methoxypyridine. All the cations showed excited-state ionization. The excited pK(a) values of these cations were determined and the results are discussed with reference to Weller's (1952) equation relating ground- and excited-state dissociation constants. 9. The pK(a) values for all ionizations undergone by the compounds examined were determined from fluorescence data. 10. Stokes shifts for the various ionic and neutral species of the compounds examined were calculated and are discussed.